WAYS TO OPTIMIZE ACCOUNTING OF ADMINISTRATIVE ENTERPRISE EXPENSES - DATSENKO, GANNA; KUDYRKO, OLENA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
Improving the efficiency of enterprise management is primarily reduced to optimizing and reducing the volume of various expenses that arises in the course of business entities activities from expenses that form the cost of products and services to expenses that are directly written off as a financial result. The constant increase in the amount and share of administrative expenses in the total amount of enterprise expensesmakes it necessary to find optimal methods of their accounting and control adapted to the needs of management and other users. Improving the accounting of administrative expenses is a component of further improving the process of managing the economic activities of enterprises in market conditions and improving their financial results. The general methodology for constructing accounting for administrative expenses by elements is similar to the methodology for constructing accounting for the costs of production activities. That is, at the first stage, cost elements are formed – material costs, labor costs, etc., and at the second stage, they are written off to financial results, which is typical for financial accounting. Conducting an internal audit of administrative expenses of the enterprise in order to establish control over their structure, size and expediency of implementation will contribute to improving the financial results of business entities activities. Maintaining accounting records of administrative expenses by groups and subaccounts, reflecting them in a consolidated document of the implementation of the system of rationing of administrative expenses will allow to improve the effectiveness of internal control in a certain sequence: determining the legality of an economic operation; ensuring the availability of primary accounting documents; ensuring synthetic and analytical accounting of administrative expenses; ensuring the correctness, validity and completeness of attribution of administrative expenses to the financial results account; analyzing administrative expenses; making managerial decisions.